The Swiss reformers Zwingli, Bullinger and Bibliander and their attitude to Islam (1520-1560) - Vehlow, Katja (Islam and Christian-Muslim relations, 1995)
The sixteenth century, the time of the Reformation in Europe, seems to be far away from modern times. Its thought seems to have lost any significance in today's world. However, as the wars in the former Yugoslavia show, prejudice and resentments can be kept alive for centuries to emerge whenever the situation is ripe again. Sixteenth‐century reformers and their writings had a lasting impact on the movements that they initiated. This is well‐known in the case of Martin Luther and his attitude towards the Jews. During the regime of the Nazis in Germany, his anti‐Jewish writings were re‐discovered and his arguments were used to justify the persecutions and killings of Jews. But it was not only Martin Luther who published polemical works. Writing against one's enemy was a kind of sport in the sixteenth century. Insults and swear words were commonly used on a scale that is somewhat embarrassing to modern ears. But what did sixteenth‐century reformers actually think or know about Islam? This paper looks at the Zurich reformers Huldrych Zwingli, Heinrich Bullinger and Theodor Bibliander and their response to Islam.